Coblopasvir and sofosbuvir for treatment of chronic hepatitis C virus infection in China: A single‐arm, open‐label, phase 3 trial. (13th October 2020) - Gao, Yanhang; Kong, Fei; Li, Guangming; Li, Cheng; Zheng, Sujun; Lin, Jianmei; Wen, Xiaofeng; Hu, Jinghua; Wang, Xiaozhong; Wu, Xiaofeng; Xing, Huichun; Jia, Jidong; et al.
Abstract: Background & Aim: An affordable, pangenotypic regimen remains as an unmet medical need for chronic hepatitis C patients in China. This single‐arm, open‐label, multicenter, phase 3 trial evaluated the efficacy and safety of coblopasvir, a pangenotypic non‐structural protein 5A (NS5A) inhibitor, combined with sofosbuvir for treating Chinese patients with chronic hepatitis C virus (HCV) infection. Methods: Treatment‐naïve and interferon‐experienced adult patients, including those with advanced fibrosis (F3) or compensated cirrhosis (F4), were treated with a universal, combinational regimen of coblopasvir 60 mg and sofosbuvir 400 mg, once daily, for 12 weeks. The primary efficacy endpoint was sustained virological response at post‐treatment week 12 (SVR12). Results: Overall, 371 patients (men, 51%; age, 47 ± 11 years; genotype 1a < 1%, 1b 48%, 2a 26%, 3a 6%, 3b 7% and 6 12%) were enrolled from 19 sites. Fifty‐one patients (14%) had F3, 39 patients (11%) had F4 and 39 patients (11%) were interferon experienced. The overall SVR12 was 97% (95% CI, [94%, 98%]) for the full analysis set and was equal to or above 90% for all predefined subsets. Ten patients (3%) experienced virological relapse and two patients did not complete follow‐up. No adverse events (AEs) occurred at a frequency ≥5%, and the most often reported AEs (≥1%) were neutropenia and fatigue. The majority of AEs were mild to moderate and transient without specific medical intervention. Conclusions: The universal, pangenotypic combo of coblopasvir plus sofosbuvir is an efficacious and safe treatment for Chinese patients monoinfected with HCV of genotype 1, 2, 3 and 6, including those with compensated cirrhosis. Lay summary: The regimen of coblopasvir and sofosbuvir is a safe and effective treatment for Chinese patients with genotype 1, 2, 3 and 6 HCV infection, including those with compensated cirrhosis. Therefore, this regimen would be a novel choice of treatment for this patient population.